Aberrant spontaneous neural activity and correlation with evoked-brain potentials in first-episode, treatment-naïve patients with deficit and non-deficit schizophrenia. (30th March 2017) - Li, Zhe; Lei, Wei; Deng, Wei; Zheng, Zhong; Li, Mingli; Ma, Xiaohong; Wang, Qiang; Huang, Chaohua; Li, Na; Collier, David A.; Gong, Qiyong; Li, Tao
Abstract: The goals of the study were to analyze spontaneous neural activity between deficit and non-deficit schizophrenia (DS, NDS) using resting-state fMRI, and to investigate the correlation of fMRI with clinical features and evoked brain potentials. The amplitude of low frequency fluctuation (ALFF) was measured in 41 DS participants, 42 NDS participants, and 42 healthy controls. ALFF in the bilateral cerebellum posterior lobe was significantly decreased in patients, while ALFF in the right fusiform gyrus and the bilateral putamen was significantly increased. In schizophrenia patients, ALFF in the right putamen positively correlated with excited/activation on Positive and Negative Syndrome Scale (PANSS-EXC/ACT). In DS patients, ALFF in the right insula was significantly increased than in controls and positively correlated with S2-P50 amplitude of sensory gating P50. ALFF in the left cerebellum posterior lobe negatively correlated with negative symptoms and withdrawn on PANSS (PANSS-NS, PANSS-WIT), ALFF in the right putamen positively correlated with PANSS-WIT. In NDS patients, ALFF in the middle temporal gyrus decreased than in controls and negatively correlated with P3b subcomponent of P300 latency. ALFF in the left cerebellum posterior lobe negatively correlated with PANSS-EXC/ACT. The middle temporal gyrus in NDS or the right insula in DS may show spatiotemporal defects. Abstract : Highlights: Spontaneous brain activity in several regions may be altered in deficit and non-deficit schizophrenia. Altered activity in the right putamen and the left cerebellum posterior lobe may be involved in the underlying neuropathology of negative symptoms in deficit schizophrenia. The latter may be involved in the underlying neuropathology excited/activation in non-deficit schizophrenia. The spatiotemporal patterning defect may be in the middle temporal gyrus in non-deficit or in the right insula in deficit schizophrenia.